Concussion and long-term cognitive impairment among professional or elite sport-persons: a systematic review. Issue 5 (27th February 2020) - Gallo, Valentina; Motley, Kim; Kemp, Simon P T; Mian, Saba; Patel, Tara; James, Laura; Pearce, Neil; McElvenny, Damien
Abstract : Introduction: Understanding whether concussion in sport is associated with worsening cognitive function in later life will likely have immediate repercussion on sports concussion prevention and management policy and sporting rules and regulations. This systematic review aims to summarise the evidence on the association between concussion sustained by professional/elite athletes and long-term cognitive impairment. Methods: Embase, PubMed and Web of Science were used to search for eligible studies. Studies including professional/elite athletes from any sport were considered. Three comparison groups were considered: internal comparison (concussed vs non-concussed athletes within the same sample); between-sport comparison (contact sport athletes vs non-contact sports ones); external comparison (athletes vs samples of the general population or population norms). Results: 14 studies were included (rugby, American football, ice hockey players, boxers and marital art fighters). The general quality of the evidence was poor. The overall evidence, weighted for type of comparison and study quality, points towards an association between sustaining a sport-related concussion and poorer cognitive function later in life in rugby, American football and boxing, although it is unclear to what extent this is clinically relevant. Data on ice hockey and martial arts were too sparse to allow conclusions to be drawn. Conclusion: High-quality, appropriately designed and powered epidemiological studies are urgently needed to assess the association between sustaining a sport-related concussion and cognitive impairment later in life. Particular emphasis should be put on the clinical translational value of findings.